Intercultural Communication on Local Wisdom and Bali's Resistance to Sharia Tourism - Valerie Avrilia Zahra Maharani; Heri Setyorini (Universitas Pendidikan Indonesia, 2024)
Bali, a highly popular tourist destination both locally and internationally, faced a controversial proposal in December 2015 to introduce sharia tourism, conflicting with its predominantly Hindu cultural heritage. The local community vehemently opposed this idea, citing discrepancies with Bali's Regional Regulation on Cultural Tourism. This research aims to explore how intercultural communication, rooted in local wisdom, influenced the Balinese people's resistance to sharia tourism. Utilizing a qualitative descriptive case study approach, primary data was gathered through in-depth interviews and observations, complemented by secondary data from literature, the internet, and documentaries. The findings reveal a positive intercultural communication dynamic between Bali's Hindu and Muslim communities, with even the Muslim residents of Bali opposing the development of sharia tourism. In conclusion, this study underscores the significance of positive intercultural communication, combined with the preservation of local traditions and wisdom, in shaping a unified cultural identity.